Fungi, Bacteria, and Viruses as Pathogens of the Fungal Community (The Fungal Community, 2005)
Fungi may be attacked by a diverse array of organisms and agents, including other fungi, bacteria, viruses, prions, and nematodes. This chapter will cover fungal, bacterial, and viral pathogens, as more is known about these systems. A great deal of literature in this area focuses on the use of these organisms for biological control. In approaching the subject of the effect of these pathogens on the fungal community, one cannot ignore the deep literature base, but it is important that it not become the focus of a chapter such as this one. Because this volume is about the fungal community, we will try to introduce systems for which there is at least some information on the effect of the pathogens on fungal populations. For many systems, this type of information is sparse or completely lacking.